Beyond Costs: How Environmental Investment Enhances Innovation in Indonesian SMEs - Odang, Nilam Kemala; Juhandi, Dany; Simanungkalit, Putri Helendgri (E-Jurnal Akuntansi, 2025)
This study examines the influence of environmental cost (EC) and environmental investment (E-INV) on environmental innovation (E-INN) in medium-scale manufacturing SMEs in Indonesia. Although many SMEs allocate budgets for environmental activities, it remains unclear whether such expenditures drive innovation. The study distinguishes between compliance-based costs and strategic investments—an approach rarely explored in the context of SMEs in developing countries. A survey of 106 SMEs was conducted and analyzed using PLS-SEM. EC has no significant effect on E-INN. In contrast, E-INV significantly and positively affects E-INN, indicating that only proactive, strategic investments enhance innovation capacity. The results confirm the Resource-Based View (RBV) by demonstrating that strategic environmental resources foster innovation. Simultaneously, the findings support institutional theory and the weak version of the Porter Hypothesis by showing that compliance spending alone is ineffective in driving innovation if it is not accompanied by strategy-oriented actions.